Diagnosing atopic dermatitis in infancy: Questionnaire reports vs criteria‐based assessment. Issue 6 (21st November 2018) - Dharma, Christoffer; Lefebvre, Diana L.; Tran, Maxwell M.; Lu, Zihang; Lou, Wendy Y. W.; Subbarao, Padmaja; Becker, Allan B.; Mandhane, Piush J.; Turvey, Stuart E.; Moraes, Theo J.; Azad, Meghan B.; Sears, Malcolm R.; et al.
Abstract: Background: Persisting atopic dermatitis (AD) is known to be associated with more serious allergic diseases at later ages; however, making an accurate diagnosis during infancy is challenging. We assessed the diagnostic performance of questionnaire‐based AD measures with criteria‐based in‐person clinical assessments at age 1 year and evaluated the ability of these diagnostic methods to predict asthma, allergic rhinitis and food allergies at age 5 years. Methods: Data relate to 3014 children participating in the Canadian Healthy Infant Longitudinal Development (CHILD) Study who were directly observed in a clinical assessment by an experienced healthcare professional using the UK Working Party criteria. The majority (2221; 73.7%) of these children also provided multiple other methods of AD ascertainment: a parent reporting a characteristic rash on a questionnaire, a parent reporting the diagnosis provided by an external physician and a combination of these two reports. Results: Relative to the direct clinical assessment, the area under the Receiver Operating Characteristic curve for a parental report of a characteristic rash, reported physician diagnosis and a combination of both were, respectively, 0.60, 0.69 and 0.70. The strongest predictor of asthma at 5 years was AD determined by criteria‐based in‐person clinical assessment followed by the combination of parental and physician report. Conclusions: These findings suggest that questionnaire data cannot accurately substitute for assessment by experienced healthcare professionals using validated criteria for diagnosis of atopic dermatitis. Combining the parental report with diagnosis by a family physician might sometimes be appropriate (eg to avoid costs of a clinical assessment).